Increased Epoxyeicosatrienoic Acids and Hydroxyeicosatetraenoic Acids After Treatment of Iodide Intake Adjustment and 1,25-Dihydroxy-Vitamin D3 Supplementation in High Iodide Intake–Induced Hypothyroid Offspring Rats - Liu, Qing; Zhang, Yue; Zhao, Hailing; Yao, Xiaomei (Frontiers in Physiology, 2021)
Background: The aim of the study was to investigate the potential role of fatty acids in high iodide intake-induced hypothyroidism and its complications, as well as in the intervention of iodide intake adjustment and 1,25(OH)2D3 supplementation. Methods: Pregnant rats were allocated to two groups: normal iodide intake (NI, 7.5 μg/day) and 100 times higher-than-normal iodide intake (100 HI, 750 μg/day). The offspring were continuously administered potassium iodide from weaning (postnatal day 21, PN21) to PN90. After PN90, the offspring were either administered iodide intake adjustment (7.5 μg/day) or 1,25(OH)2D3 supplementation (5 μg·kg−1·day−1), or both, for 4 weeks. Thyroid function tests (FT3, FT4, TSH, TPOAb and TgAb), blood lipids (TG, TC, FFA and LDL-C) and VD3 levels were detected by ELISA. Cardiac function was measured by echocardiography. Blood pressure was measured using a non-invasive tail-cuff system. Serum fatty acids profile was analyzed by LC–MS. Results: In the continued 100 HI administration offspring rats, the levels of 8,9-DHET and TXB2 were decreased, while those of PGJ2, PGB2, 4-HDoHE, 7-HDoHE, 8-HDoHE and 20-HDoHE were increased. Significant correlations were found between PGB2, 8,9-DHET, 7-HDoHE levels and thyroid dysfunction, between PGJ2, 20-HDoHE, PGB2, 8,9-DHET levels and cardiac dysfunction, between PGJ2, 20-HDoHE levels and hypertension, between 4-HDoHE, 8-HDoHE, TXB2 levels and dyslipidemia, and between PGB2 and decreased VD3 level. After the treatment of iodide intake adjustment and 1,25(OH)2D3 supplementation, the levels of 16-HETE, 18-HETE, 5,6-EET, 8,9-EET, 11,12-EET, 14,15-EET, PGE2, 5-oxo-ETE and 15-oxo-ETE were increased. Significant associations between PGE2, 16-HETE, 18-HETE and improved thyroid function, between 5,6-EET, 11,12-EET, 14,15-EET, 16-HETE, 15-oxo-ETE and atenuated dyslipidemia were detected. Conclusion: The increased PGs, HDoHEs and decreased 8,9-DHET, TXB2 levels might take part in the progression of cardiac dysfunction, hypertension and dyslipidemia in high iodide intake-induce hypothyroidism, increased EETs and HETEs might be helpful for ameliorating these complications after iodide intake adjustment and 1,25(OH)2D3 supplementation. Keywords: eicosanoids, iodide intake adjustment, 1,25(OH)2D3, hypothyroidism, cardiac dysfunction, hypertension, dyslipidemia.